Natural Therapeutics in Aid of Treating Alzheimer’s Disease: A Green Gateway Toward Ending Quest for Treating Neurological Disorders - Bhat, Basharat Ahmad; Almilaibary, Abdullah; Mir, Rakeeb Ahmad; Aljarallah, Badr M.; Mir, Wajahat R.; Ahmad, Fuzail; Mir, Manzoor Ahmad (Frontiers in Neuroscience, 2022)
The current scientific community is facing a daunting challenge to unravel reliable natural compounds with realistic potential to treat neurological disorders such as Alzheimer’s disease (AD). The reported compounds/drugs mostly synthetic deemed the reliability and therapeutic potential largely due to their complexity and off-target issues. The natural products from nutraceutical compounds emerge as viable preventive therapeutics to fill the huge gap in treating neurological disorders. Considering that Alzheimer’s disease is a multifactorial disease, natural compounds offer the advantage of a multitarget approach, tagging different molecular sites in the human brain, as compared with the single-target activity of most of the drugs so far used to treat Alzheimer’s disease. A wide range of plant extracts and phytochemicals reported to possess the therapeutic potential to Alzheimer’s disease includes curcumin, resveratrol, epigallocatechin-3-gallate, morin, delphinidins, quercetin, luteolin, oleocanthal, and other phytochemicals such as huperzine A, limonoids, and azaphilones. Reported targets of these natural compounds include inhibition of acetylcholinesterase, amyloid senile plaques, oxidation products, inflammatory pathways, specific brain receptors, etc. We tenaciously aimed to review the in-depth potential of natural products and their therapeutic applications against Alzheimer’s disease, with a special focus on a diversity of medicinal plants and phytocompounds and their mechanism of action against Alzheimer’s disease pathologies. We strongly believe that the medicinal plants and phytoconstituents alone or in combination with other compounds would be effective treatments against Alzheimer’s disease with lesser side effects as compared to currently available treatments.